P763 Quality of life in Paediatric inflammatory bowel disease Patient: How well do we understand patients?. (16th January 2018) - Kim, S; Park, S; Kang, Y; Koh, H
Abstract: Background: Inflammatory bowel disease (IBD) is a chronic relapsing disease which can negatively affect the quality of life (QOL) of the patient. Improving QOL is one of the important therapeutic targets of IBD, and in order to do so, it is essential to assess one. In this study, we compared the actual QOL of the patients with the QOL of the patients evaluated by their medical staffs or caregivers and estimated how well they know the patients. Methods: Sixty-two children and adolescent IBD patients followed at Severance Children's Hospital were enrolled in this study. The patients themselves answered the questionnaire (IMPACT-III) at the hospital visit. On the same day, parents, physicians and IBD nurse conducted the same questionnaire for each patient. The actual total IMPACT-III score of the patients themselves and each subdomain scores were compared with the IMPACT-III scores conducted by guardians and medical staffs. Results: The intraclass correlation coefficient (ICC) of total IMPACT-III score was the most relevant between father and patient (0.824, 95% confidence interval 0.495–0.938) and was higher in order of mother (0.689, 95% confidence interval 0.474–0.816), physician (0.625, 95% confidence interval 0.386–0.772), and nurse (0.499, 95% confidence interval 0.179–0.694). Among the subdomain scores, bowel symptom subdomain was the most relevant one between patent and others whereas "treatment and intervention" was the least relevant subdomain. Both parents and medical staffs assessed the patients' QOL lower than the QOL assessed by patients themselves. The differences of IMPACT-III scores to patients were −10.09 ± 17.86 for physician, −9.87 ± 15.80 for mothers, −5.72 ± 17.04 for nurse and −3.81 ± 11.82 for fathers. Conclusions: The QOL of the patients estimated by the caregiver or the medical staffs showed a relatively high correlation with the QOL of the patients documented by patients themselves. However, both medical staffs and caregivers tend to underestimate the QOL of the patients.